Trends and Determinants of Nosocomial Infection among Hospitalised Patients at Koforidua Regional Hospital. - Alormenyo, N.M. (University of Ghana, 2019)
Background Nosocomial infections are a major public health problem worldwide and are on the increase despite significant efforts by hospital infection control measures. Nosocomial infection comprises infection occurring in a patient who is receiving treatment in a health care settings. Infection acquired by health care workers and people visiting the hospital is considered nosocomial infection. These infections affect about 2 million people globally resulting in 5% to 15% of them spending longer stay days in the hospital. In sub-Saharan Africa, incidence of nosocomial infections ranges from 2-49% with patients in intensive care units having up to 35.6%. Objectives. The objectives of this study were to provide an understanding of the trends and factors associated with nosocomial infection and also to identify the causative agents of these infections by tracing them in the microbial records for the past three years. Methods. Electronic data of all patients who were admitted and went through any invasive procedures at Koforidua Regional Hospital between the years 2016-2018 were reviewed. Any post –surgery purulent discharges, abscess, and inflammation at the site of surgery, positive urine culture of about 1 or 2 species with at least 10 bacteria / ml with or without clinical manifestation after catheterization were included in the study. Again, respiratory signs such as couth, purulent sputum, new infiltrate on the chest and radiography consistent with infection after or during tracheotomy and any inflammation, lymphagitis and purulent discharges at the site of vascular puncture, cepticaemia, fever, rigor and at least one positive blood culture suffered by a patient University were also included in the study. All patients of different ages and sex group that went through any invasive procedures in the hospital within the year under review were included. Results. The results from the study showed a 1.2% prevalence of nosocomial infection in Koforidua Regional hospital. It was also observed from the results that patients whose ages were more than 40 years had a nosocomial infection prevalence ranging from 1.2% to 2.1%. With the trends of infection by number of days hospitalized, it was found that patients who were on admission for less than 13 days had infection prevalence between 1% to 4.5% as compared to 13.6 % for patients who were admitted for more than 14 days. In the environment where service was provided, results showed 9.75% infection prevalence at the ICU, 1.49% in female surgical ward and 0.95% in male surgical ward. With the payment methods, results revealed 0.82% infection prevalence for patients who used cash to pay for health service delivery by themselves and 1.37% for patients who depended on the National Health Insurance Scheme (NHIS) for payment. Finally, staphylococcus and streptococcus were found to be the most prevalent nosocomial bacteria in the facility. In conclusion, the more a person aged, the more the immunity reduced and the higher the vulnerability for infection. Infection in the hospital was also determined by the number of days a patient stayed in the facility. Again, because more potent and quality drugs were purchased by patients who used cash, their level of infection reduced more drastically. Finally, more females were infected than males.
MPH.
Keywords: Nosocomial Infection; Koforidua Regional Hospital